Identification and typing of Salmonella enterica serotypes isolated from guinea fowl (Numida meleagris) farms in Benin during four laying seasons (2007 to 2010) - BOKO, KADOÉITO CYRILLE; KPODEKON, TCHOKPONHOUE TCHEGNINOUGBO MARC; DUPREZ, J.-N; Imberechts, Hein; Taminiau, Bernard; Bertrand, Sophie; MAINIL, J.G (My University, 2013)
The main problem for the local guinea fowl (Numida meleagris) traditional farming and raising system in north-east Benin is the high mortality rate of the keets (up to 70%) due to a combination of climatic, nutritional, hygienic and infectious causes. The present study was carried out to identify and compare the isolates of Salmonella enterica from necropsied keets, laying guinea fowl, surrogate hen mothers, other contact animal species and farmers during four laying seasons (2007 to 2010). S. enterica belonging to eight different serotypes (Adelaide, Farakan, Kingston, Legon, Luke, Oakland, Sangalkam and Teshie) and one untypable isolate were isolated from 13 to 19% of the necropsied keets. The serotypes Adelaide, Farakan, Luke, Sangalkam and Teshie and the untypable isolate were isolated in only one township during 1 year of sampling, while serotypes Oakland, Legon and Kingston were present in two to three townships for 2 to 3 years of sampling. Serotypes Farakan, Kingston, Legon, Oakland and Sangalkam were also isolated from faecal samples of laying guinea fowl and/or surrogate domestic fowl hen mothers. Further comparison by pulsed-field gel electrophoresis and virulotyping provided evidence for their clonality within each of those five serotypes and therefore for the adult guinea fowl and/or hens as the most probable origin of contamination of the keets. The antibiotic resistance profiles, with all isolates resistant to oxacillin, sulfamethoxazol and colistin, emphasize the rise of antibiotic resistance in salmonellas from guinea fowl in this area and the need for alternative therapy policies for these birds.
Keywords: Salmonella - guinea fowl - serotypes - Pulsed Field Gel Electrophoresis - virulotyping